The influence of mineralogical composition of soil on the consolidation coefficient value - Karina Zabłocka; Marzena Lendo-Siwicka; Grzegorz Wrzesiński (Acta Scientiarum Polonorum. Architectura)
This paper involves the results of oedometric tests carried out on four model samples with different content of expansive clay minerals, subjected to different stresses. The research aimed to determine the impact of consolidation pressure on the consolidation coefficient for cohesive soils with different mineral composition. Main factors influencing correlation between consolidation coefficient and consolidation pressure (Cv–p) trends turned out to be mechanisms controlling changes in soil volume (mechanical or physicochemical), which is different for expansive and non-expansive soils.